c-Myb inhibits myogenic differentiation through repression of MyoD - Kašpar, Petr; Pajer, Petr; Sedlák, David; Tamaoki, T; Dvořák, Michal (Experimental cell research, 2005)
c-Myb, known to play a central role in hematopoiesis, is also an important factor involved in myogenesis. Here, we found that the c-myb gene is expressed in proliferating C2C12 myoblasts and turned off in differentiating cells. Detailed analysis of c-myb RNAs revealed that the cell density is the essential factor determining c-myb expression. Both c-myb and its alternatively spliced form c-mybE9A RNAs are down-regulated in confluent cells. Constitutive expression of exogenous c-myb in C2C12 cells inhibits their terminal differentiation. It is shown that the c-Myb protein physically interacts with MyoD, the key regulator of myogenesis, and inhibits MyoD-dependent transcription. The interaction domains are the DNA binding domain of c-Myb and the bHLH motif of MyoD. Our data suggest that in proliferating cells c-Myb binds MyoD and inhibits its transcriptional activity until cell-cell contacts are established and c-myb expression is switched off. Thus, the c-Myb protein may be one of factors ensuring that proliferating myoblasts remain undifferentiated.
Keywords: financování organizované; Animals; myši inbrední C3H; Proto-Oncogene Proteins c-myb; Cell Count; Mice, Inbred C3H; buněčné linie; protoonkogenní proteiny c-myb; myogenní regulační faktory; vazba proteinů; buněčná diferenciace; Mice; myši; Cell Line; Financing, Organized; myoblasty; Myogenic Regulatory Factors; počet buněk; Cell Differentiation; promotorové oblasti (genetika); zvířata; Myoblasts; Promoter Regions, Genetic; MyoD Protein; Protein Binding